PERSEPSI MASYARAKAT PADA BERITA HOAKS MEDIA ONLINE TENTANG VAKSINASI COVID-19 DI KABUPATEN LABUHANBATU (Studi Kasus: Desa Meranti Paham) - Ari Kurnia, Solihah Titin Sumanti, Syahrul Abidin (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2022)
Meranti Paham Village in dealing with hoaxes that have been circulating and spread in online media. In this study,there are various formulations of the problem including what online media is used, what hoax news is circulating,and what is the public's view of hoax news. This study uses a qualitative method with a phenomenological approachthrough in-depth interviews as well as observation and documentation. The results of this study are that hoax newsabout the Covid- 19 vaccination circulating are such as the Covid-19 vaccination causing early death, infertility,being more susceptible to viruses, containing microchips, and vaccines made from non-halal materials. Whatsapp,facebook, and youtube are online media that are often used by the people of Meranti Paham Village. With theinvolvement of researchers in interviews and direct observations to Meranti Paham Village, researchers provideinput to the Meranti Paham Village community, especially those interviewed by researchers to be more careful inresponding to a news. With the circulation of hoax news regarding the Covid-19 vaccination, the people in MerantiPaham Village, who initially refused to be vaccinated, eventually joined the vaccination program as well. So it canbe said that the people in Meranti Paham Village are not easily influenced by hoax news for too long.